All-Dielectric Nanoresonators for χ(2) Nonlinear Optics - Gigli, Carlo; Marino, Giuseppe; Borne, Adrien; Lalanne, Philippe; Leo, Giuseppe (Frontiers in Physics, 2019)
Metal-less nanophotonics offers new opportunities for non-linear optics with respect to optical waveguides and microresonators, taking advantage of the progress within nanofabrication to boost the development of subwavelength Mie-type structures. Here, we review recent results on second harmonic generation with semiconductor nanoresonators, focusing on their scattering features in terms of efficiency and control over radiation patterns. First, two theoretical models are comparatively discussed with a view to possible improvements in analysis and design. Then, some relevant experiments are reported, and the origin of the χ(2) generation is discussed, outlining the main open topics to investigate in the near future and the advantages offered by these nanostructures to the development of novel photonic devices.